Controlling Invasive Exotic Plants in North Florida Forests - Chris Demers; Alan Long; Rick Williams (EDIS, 2012)
Invasive non-native organisms are one of the greatest threats to the natural ecosystems of the United States. Invasive plants reduce biodiversity, encroach on endangered and threatened species, and rob native species of habitat. This revised 8-page fact sheet describes many of the current methods used to manage some of the more common and troublesome invasive exotic plants in north Florida forests. Written by Chris Demers, Alan Long, and Rick Williams, and published by the UF Department of School of Forest Resources and Conservation, January 2012.